Energy-power parameters analyses of rotary mixing device - Вознюк, В’ячеслав Тарасович; Кваша, Максим Володимирович; Мікульонок, Ігор Олегович (Eastern-European Journal of Enterprise Technologies, 2012)
Are investigated energy-power parameters of the mixing process in a rotary mixer with oval rotors. During the analysis movement of a received composition in a blending chamber not only in circular, but also in an axial direction was considered